Review of the field environmental sensing methods based on multi-sensor information fusion technology - Zhang, Yuanyuan; Zhang, Bin; Shen, Cheng; Liu, Haolu; Huang, Jicheng; Tian, Kunpeng; Tang, Zhong (International Journal of Agricultural and Biological Engineering, 2024)
Field environmental sensing can acquire real-time environmental information, which will be applied to field operation, through the fusion of multiple sensors. Multi-sensor fusion refers to the fusion of information obtained from multiple sensors using more advanced data processing methods. The main objective of applying this technology in field environment perception is to acquire real-time environmental information, making agricultural mechanical devices operate better in complex farmland environment with stronger sensing ability and operational accuracy. In this paper, the characteristics of sensors are studied to clarify the advantages and existing problems of each type of sensors and point out that multiple sensors can be introduced to compensate for the information loss. Secondly, the mainstream information fusion types at present are outlined. The characteristics, advantages and disadvantages of different fusion methods are analyzed. The important studies and applications related to multi-sensor information fusion technology published at home and abroad are listed. Eventually, the existing problems in the field environment sensing at present are summarized and the prospect for future of sensors precise sensing, multi-dimensional fusion strategies, discrepancies in sensor fusion and agricultural information processing are proposed in hope of providing reference for the deeper development of smart agriculture. Key words: multi-sensor; information fusion; field environmental sensing; fusion methods; smart agricultureDOI: 10.25165/j.ijabe.20241702.8596Citation: Zhang Y Y, Zhang B, Shen C, Liu H L, Huang J C, Tian K P, et al. Review of the field environmental sensing methods based on multi-sensor information fusion technology. Int J Agric & Biol Eng, 2024; 17(2): 1–13.